SYNTHESIS OF ACRYLAMIDE COPOLYMERS WITH IMPROVED VISCOSITY CHARACTERISTICS - A, Аllamurtova; O, Tanatarov; A, Sharipova; Аbdikamalova, Aziza; Kuldasheva, Shaxnoza (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2024)
Abstract: The prerequisite for this study was the influence of the pH of the medium on the copolymerization process and the characteristics of the copolymers of itaconic acid and acrylamide. The aim of the work was to study this effect on the molecular weight of copolymers and their yield. The methodology included copolymerization of IR and AA at different pH values and different mole ratios of monomers, as well as analysis of the molecular characteristics of copolymers and product yield. The obtained data demonstrate that copolymers synthesized under neutral and slightly alkaline conditions have higher molecular weights and yields compared to an acidic medium, which opens up new prospects for tuning the synthesis of copolymers with desired properties.